The initiation phase of somatic embryogenesis: what we know and what we don't - Fehér, Attila (Acta Biologica Szegediensis, 2008)
Somatic plant cells are not terminally differentiated and can therefore regain totipotency and initiate embryo development under appropriate conditions. Although this phenomenon is well known for more than 50 years, the details are still mysterious as we do not know why certain genotypes, explants or cells are more amenable for somatic embryogenesis than the others. It is also not know why so many different conditions can be used to initiate somatic embryogenesis and what are the key molecular steps being common in all cases. Recent progress in plant molecular and developmental biology now allows us to establish new hypotheses on the way of transition of somatic cells to the embryogenic state. One of the possible hypotheses is presented in this short review.